Assessment of a multistage system based on electrocoagulation, solar photo-Fenton and biological oxidation processes for real textile wastewater treatment - Diego R. Manenti (2014)
The performance of a multistage treatment system for textile wastewater was investigated in this study. The processes of electrocoagulation (EC), photo-Fenton oxidation, and activated sludge biological degradation were integrated in batch mode. The integrated treatment system performance was assessed according to three response variables: dissolved organic carbon (DOC), chemical oxygen demand (COD) and biodegradability index. Based on preliminary tests, the EC-based wastewater treatment was suitable as the first stage of the integrated treatment system, followed by the photo-Fenton process. A lab photo-reactor was used to assess the influence of photo-Fenton variables on the process performance. Based on the better lab photo-Fenton reactor conditions, the improvement of some biological indicators related to the organics biodegradability of treated wastewater was investigated in a pilot-scale photoreactor. An activated sludge-based biological reactor at lab-scale was used as a final treatment stage, in order to achieve the legislated limits for discharge into water bodies. Partial degradation of the organic pollutants was achieved by the EC process, with a 36% reduction in COD. In the second treatment stage, a 70% biodegradability index was attained by setting the photo-Fenton reaction conditions at 100 mg Fe2+ L-1, pH 2.8, 12 mM H2O2 and 6.9 kJ L-1 accumulated energy. Finally, a residual COD of 139 mg O-2 L-1 was achieved at the outlet of the biological process, which is below the maximum limit established by the Portuguese legislation.